Cities, towns, and poverty: Migration Equilibrium and income distribution in a Todaro-type model with multiple destinations - Luc J. Christiaensen; Joachim De Weerdt; Ravi Kanbur (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
Should public investment be targeted to big cities or to small towns, if the objective is to minimize national poverty? To answer this policy question we extend the basic Todaro-type model of rural-urban migration to the case of migration from rural areas to two potential destinations, secondary town and big city. We first derive conditions under which a poverty gradient from rural to town to city will exist as an equilibrium phenomenon. We then address the policy question and show how the answer depends on the migration response, where the poverty line lies relative to incomes in the three locations, and at times also the poverty index itself. In particular, we develop sufficient statistics for the policy decisions based on these income parameters and illustrate the empirical remit of the model with long running panel data from Kagera, Tanzania. Further, we show that the structure of the sufficient statistics is maintained in the case where the model is generalized to introduce heterogeneous workers and jobs. Overall, the findings confirm that, given migration responses, national poverty outcomes are not immune to whether urban employment generation takes place in the towns or the city.
Keywords: 330; Secondary Towns versus Big Cities; Poverty Reduction; Poverty Gradient; Todaro Model; Migration Equilibrium; Equilibrium Income Distribution